Deep structure of the North-East part of the Black Sea based on the results of seismogravity modeling - Kozlenko, Yu.V. (Reports of the National Academy of Sciences of Ukraine, 2015)
On the basis of tomographic calculations along the DSS profile No. 17, a density model with the computations of anomalies of the gravity field in free air is built. It is shown that the Earth's crust in a section of the profile by the thickness and the distribution of V and ρ is referred to the subcontinental type. The complex interpretation of the seismic and gravity models grounds that the features of the structure of the north-east part of the Black sea near the coast of the Crimean peninsula in the section of the profile are conditioned by the processes of continental crust basification.